Enydra fluctuans Lour. - an addition to the flora of Kerala, India - Jose, Sojan; Suresh, V.; Prakashkumar, R.; Madhusoodanan, P. V. (Journal of the Bombay Natural History Society (JBNHS), 2015)
No Abstract.